Deteksi Dini Gangguan Jiwa pada Remaja SMK YPPP Wonomulyo - Nurfadila, Nurfadila; Ambo Hamzah, Idawati (Yayasan Mandar Indonesia, 2022)
Adolescents are unique individuals with all the developmental processes that they must go through both physically and psychologically, adolescence is also a transitional period and also a difficult period for adolescents so that it is likely to be a change in behavior related to the developments that occur in these adolescents. The benefits of early mental detection in adolescents are to provide knowledge and understanding as well as attention to the condition of adolescent development, namely the physical and motor conditions that exist within the individual to avoid and cope with the occurrence of disturbances. Early detection in adolescents is also a form of prevention from the start against indications of impending disturbances. This study uses a descriptive research methodology. With a population of 272 students in class X, and 290 students in class XII, the research sample is 550 students with inclusion criteria, students who study at SMK YPPP Wonomulyo and are in class X and XI. Exclusion criteria, students who were not present at the time of the study. From the results of a study with 550 respondents the problem of early detection of adolescent mental disorders, the highest was at an abnormal percentage, namely anxiety and depression as much as 45%. certain factors.